2014 IEEE Globecom Workshops (GC Wkshps) 2014
DOI: 10.1109/glocomw.2014.7063641
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicle as communication relay for autonomous underwater vehicle — Field tests

Abstract: Abstract-This paper describes field experiments with an X8 Unmanned Aerial Vehicle (UAV) operating as a wireless communication relay while loitering over a REMUS 100 Autonomous Underwater Vehicle (AUV) being at the ocean surface. The paper describes the design of the communication relay payload, network configuration, optimal flight conditions and UAV antenna mounting, and experimental results. Experiments were conducted under less than ideal conditions with rain and turbulent winds leading to unfavorable roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…The navigation system is tested for a single UAV. 3) An experimental test when a UAV acts as a relay to transmit information from an underwater vehicle to a ground base station is described in [142]. In this setup, a UAV moves in a circular way around an underwater vehicle with the speed of 18m/s.…”
Section: F Other Relevant Testbedsmentioning
confidence: 99%
“…The navigation system is tested for a single UAV. 3) An experimental test when a UAV acts as a relay to transmit information from an underwater vehicle to a ground base station is described in [142]. In this setup, a UAV moves in a circular way around an underwater vehicle with the speed of 18m/s.…”
Section: F Other Relevant Testbedsmentioning
confidence: 99%
“…In those research IEEE 802.11 (WiFi) network devices are used. This results in high bandwidth at the expense of range [4], [5].…”
Section: State Of Knowledgementioning
confidence: 99%
“…In this work, they showed that high throughout can be achieved using two-hop communications. Johansen et al [28] described the field experiment with a fixed wing UAV acted as a wireless relay for Underwater Vehicle. They only tested the download data rates.…”
Section: Related Workmentioning
confidence: 99%